Peningkatan Prestasi Belajar Matematika Melalui Alat Peraga Puzzle Box Pada Materi Bangun Datar Di Kelas IV MIN Ar Rahman Kota Langsa - Jannati, Putri; Malahati , Fildza; Romadhon , Kharisma (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
This research is expected to improve student learning achievement in mathematics (MTK). Low student learning outcomes and students' lack of understanding of the subject matter as a result of conventional teaching methods that do not use real media have been accepted as the biggest problems. This has solved the two-cycle Classroom Action Research (CAR) strategy based on the Kemmis and McTaggart model. Preparation, implementation of activities, observation, and reflection are the four steps that make up each cycle. The teaching aids used are Puzzle Box models. The average value of students increased significantly, based on research statistics. The average value of students increased from 61.4 in the pre-cycle stage to 69.2 in cycle I, and then to 78.4 in cycle II. At that timhje, the percentage of students who achieved the learning completeness standard increased from 36% at the beginning of cycle II to 88% at the end of the cycle. The results presented show how the use of teaching aids can improve conceptual understanding, research motivation, and engagement in the academic learning process. Teaching aids have been proven effective in improving the quality of student learning outcomes when used as learning materials.